Effect of type and concentration of hydrocolloids on the rheology, water mobility, and 3D printing properties of pitaya fruit-based ink - Omedi, Jacob Ojobi; Chen, Cheng; Uriho, Angelo; Zhang, Shuning; Liang, Li; Zou, Qibo; Xu, Yan; Zhang, Min; Wang, Yuchuan; Huang, Weining (Frontiers in Nutrition, 2026)
In this study, the effects of three hydrocolloids, xanthan gum (XG), arabica gum (AG) and carboxymethylcellulose (CMC), at two concentrations on the rheological, water mobility and 3D printing characteristics of pitaya fruit-based inks were investigated. The results showed that hydrocolloids restricted water mobility by increasing the immobilized water (T22) with higher content in CMC (97.5%−98.01%), AG (96.28%−97.26%), and XG (95.35%−95.38%), at 9 g/100 g than 6 g/100 g hydrocolloid concentration in the hydrocolloid-fruit inks. The rheological properties, based on the apparent viscosity, G′ and G′′ were increased in the pitaya fruit inks, especially in presence of CMC, then AG and XG at higher than lower concentration. Moreover, the printing precision improved, while the textural profile based on hardness and resilience increased, adhesiveness and springiness decreased, and influenced the color profiles in the hydrocolloid-fruit ink printed objects containing XG, then CMC and AG at 9 g/100 g than 6 g/100 g concentration. These changes were attributed to the increased water holding capacity in presence of different hydrocolloids at higher concentrations which reduced water mobility, slow water molecules re-orientation, and increased pseudoplastic and solid-like (G′ higher than G′′) character in the hydrocolloid-fruit inks: this could have led to the better retention of the 3D printed structure. The results presented demonstrated the influence of different types of hydrocolloids at varying concentrations on altering the physicochemical and technological properties of high moisture content fruit substrate-based inks for 3D food printing applications. In addition, these findings pave the way for further studies on the development of natural and health-promoting fruit substrate-based 3D printed snack food products.